Hymenoplasty as a Means of Facilitating Marriage: A Comparative Study of Islamic Family Law Fatwas and Indonesian National Law - Alex Kusmardani; Asep Rozali; Sofyan Mei Utama; Usep Saepullah; Asmad Ali Dulatif (CV RIFAINSTITUT, 2026)
This study is motivated by the increasing practice of hymenoplasty as a response to social, cultural, and psychological pressures related to the concept of virginity, as well as the absence of explicit legal regulation in Indonesia and differing views in Islamic law. The study aims to analyze the legal status of hymenoplasty from the perspective of contemporary Islamic family law fatwas and Indonesian national law, and to assess its relevance as a means of facilitating marriage. This research employs a library research method with conceptual, comparative, and statutory approaches. Data are analyzed using content analysis and comparative analysis of relevant fatwās and legal regulations. The findings reveal divergent views among scholars: some strictly prohibit the practice due to moral concerns and the potential for deception, while others permit it conditionally to protect honor and prevent greater harm. Within the Indonesian legal system, hymenoplasty is not explicitly regulated but is generally permissible as long as it complies with ethical standards, professional guidelines, and social norms. In conclusion, the legal status of hymenoplasty is contextual and may be conditionally justified as a means of maintaining marital harmony, provided that it adheres to ethical limitations and moral responsibility